Investing financial capital in risky business conditions through probability assessment and distribution - Dino Baricevic; Irijana Rajkovic; Sara Fuchs (UTMS Journal of Economics, 2022)
Investing financial capital is almost always risky, there is no safe investment, and any unplanned situation in the future, uncertainty or sudden events can mean risk. To assess risk and protect themselves from it, investors resort to probability distribution. From the above, the subject of the paper is derived, which is the investment of capital in conditions of risk with reference to the assessment and distribution of value. Distribution is marked by all possible outcomes with the assigned probability of each result, and the aim of the scientific work is to explain how investors implement this mathematical-statistical method. The purpose of the scientific paper is to present the results of research based on read and processed literature, in foreign and domestic articles. The thesis put forward by the authors in their scientific paper is that "There is no method that will completely reduce the risks, because market risk is impossible to influence". According to the authors, the risk is influenced by many variables, the more variables - the higher the risk, and in order for it to be precisely defined in the investment business, it is necessary to know its core, it is necessary to assess it. Any unplanned situation in the future, uncertainty or sudden events can mean risk. The probability distribution, on the other hand, is a list of all possible outcomes with the assigned probability of each outcome, and its most common parameters are the expected rate of return and standard deviation. Foreign authors mostly see investing capital in conditions of risk as an opportunity for investors who need to know at what point to invest, and therefore propose new theories. Surveys dealing with probability estimation and distribution were selected.
Keywords: F01; Z32; 330; capital investment; risk; valuation; distribution value of capital; portfolio